Deceased kidney transplantation with thymoglobulin versus anti-IL2R monoclonal antibody induction - A paired kidney analysis - Oliveira, Cláudia Maria Costa de (2011)
Purpose: Thymoglobulin is an important polyclonal antibody used in kidney transplantation as an induction therapy, and it has been asso- ciated to a decrease in delayed graft function and acute rejection rates. The authors used a paired kidney analysis to compare thymoglobulin with other induction therapies, in order to minimize the donor variabilility and bias. Methods: All paired kidneys from deceased donors during the period 2006-2008, where one kidney was allocated to a patient receiving thymoglobulin (group1) and its mate allocated to a pa- tient receiving anti IL-2R monoclonal antibodies (group 2) were assessed in this retrospective study. To investigate the impact of induction therapy, we investigated the delayed graft function rates (DGF), acute rejection (AR) and renal function in the first year after the transplant (Tx) in the paired kidney subjects. Results: A total of 94 Txs were investigated: mean age: 38.4 years, being 60.6 % male and with average dialysis time of 4.11 yrs. No statistically significant difference was found between both groups in relation to the recipient age, gender, HLA mismatches, PRA, cold ischemia time (CIT). Immunosuppressive protocol consisted to mofetil mycophenolate plus calcineurin inhibitors (tacrolimus in 88.3% of patients) in both groups, and steroids in 62% of patients. Deceased donor characteristics were: 63.8% male, mean age 30.9 ys, serum creatinine 1.17 mg/dl. The most important causes of death were trauma in 48.9% and cerebrovascular accident in 19.1% donors. The magnitude of renal function at 3, 6 and 12 post-Tx months and the DGF rate (56.6% vs 63.0%) were not statistically different between both groups. The rate of any AR report within 1 post-Tx year was significantly lower in the Thymo group (19.6 vs 45.7%; p = 0.008), and the incidence of CMV disease was similar in both groups (10.9 vs 15.2%; p = 0.535). Conclusion: Thymoglobulin was associated to a significant reduction in 1 yr-acute rejection rate in this cohort of paired kidneys, but without presenting a decreased DGF rate. There was no impact on renal function/CMV disease in the 1st post-Tx year.